Glosy letniego dnia i inne utwory - Shaw, Irwin, 1913-1984. (Katowice : Wydawnictwo "Ksiaznica", 1993)
Polish translation of Irwin Shaw's "Voices of a Summer Day."
Translation of: Voices of a summer day.